رياضة الرّمي حكمها وفضلها وشروط المسابقة فيها في الفقه الإسلامي - النحوي, عيسى (جامعة الوادي - University of Eloued, 2023)
ملخص: يعتبر الرمي من الرياضات الشريفة التي حث الشرع الحكيم على تعلمها وجعلها من الأعمال الفاضلة، وذم من تركها بعدما علمها، ففي ممارستها تقوية للمسلم، وتدريب له؛ وتنشيط لبدنه. وترويح لنفسه، وتهدف هذه الدراسة للإجابة عن التساؤلات التالية: ما حكم رياضة الرمي؟ وما فضل ممارستها؟ وما شروط المسابقة فيها؟ وقد سلكت في الدراسة منهجا اعتمدت فيه على ما جاء في المذاهب الأربعة في الموضوع. وتوصلت لنتائج أهمها: أن المسابقة في الرمي بالسهام وغيرها بغير عوض جائزة باتفاق. وتجوز بعوض في السهام فقط عند الجمهور، وبعوض في غير السهام من آلات الرمي، عند الشافعية. ونظرا لأهمية الرمي، وأهمية ممارسته على نحو صحيح عادل فقد وضع الفقهاء شرائط لصحة أخذ العوض عند المسابقة فيه، ليخلو من المحاذير وليتحقق الغرض المقصود من فعله.Abstract: The sport of shooting is considered one of the honorable sports that Islamic law encouraged us to learn. And made it one of the virtuous acts, and censured those who left it after learning it. Practicing shooting sports strengthens the Muslim, trains him, and revitalizes his body. This study aims to answer the following questions: What is the ruling of shooting sports? What are the advantages of practicing it? What are the competition conditions? The study uses an approach based on the Four Juristic Schools. The study results are the following: Competitions in archery and other shooting sports without prizes are permissible by the consensus of scholars. Prizes are permissible only in archery (throwing arrows) competitions permissible by the consensus of scholars. However, Shafi'i scholars view that it is permissible to take prizes in other shooting tools competitions. Considering the importance of shooting sports and the importance of practicing it correctly, the jurists set conditions to take valid prizes when competing in shooting sports. This is to avoid prohibitions and to fulfill its purpose.
مقال
Keywords: رياضة ؛ رمي ؛ مسابقة ؛ فقه إسلامي; sports ; shooting sports ; competition ; Islamic jurisprudence